Mentoring Article Writing in Economics and Business: Providing Personal Support to Improve Quality Scientific Article Writing for IAIN Kediri Lecturers and Students - Latif, Sahraman D. Hadii; Arifin, Sirajul; Zunaidi, Arif; Mutafarida, Binti; Zainuddin, Moh. (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This service aims to provide personal support for writing quality scientific articles to lecturers and students at the Kediri State Islamic Institute (IAIN) in the fields of economics and business. The service method is carried out through a series of mentoring activities, which include individual consultation sessions, personal guidance, and direct feedback. The results show an increase in scientific article writing skills, an understanding of the publication process, and increased motivation to contribute to academic literature. The aim of the service is to improve the quality of academic publications at IAIN Kediri, strengthen the research capacity of lecturers and students, and increase contributions to the development of economics and business, especially in the Islamic context.